Prioritas Pemberitaan Injil Dalam 2 Korintus 4:1-6 - Lilis Setyarini (Jurnal Teologi dan Pelayanan Kerusso, 2017)
Priority Evangelists will be the object of study in this chapter focus on letter 2 Corinthians 4: 1-6. Where this topic is divided into four parts: Basic Services evangelist is because of God's mercy and receives the service. The second part talks about Exemplary Evangelists who should not lose heart in preaching the Gospel, Refuse act sneaky hidden and does not apply in the gospel. The third is the method in which the Not Faking Preaching the Word of God, Expressing Truth, Submit Yourself to Consider All People in the Face of God. Then the fourth is the focus of the preaching of the Gospel, in which the preacher must declare Jesus Christ as perso nal Lord and Herald as a servant who proclaim the greatness of Christ. Furthermore, the final section concludes with Affirmation of the news it self is Personal Testimony of Paul (of the light shine in the dark.